Cedera Saraf Setelah Anestesi Neuraksial Nerves Injury Post Neuroaxial Anesthesia - Doso Sutiyono (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2014)
Neural injury post neuroaxial anesthesia procedure is a rare complication but feared by many anesthesiologists. Neural injury incidence range is 0,03 to 0,1% among all neruaxial block patients. Neural injury is happened due to infection, needle-trauma to vertebrae or vertebral neural cord directly, medulla spinalis ischaemia or neurotoxicity. Most causes of neural injury are hematoma and infection. Whenever suspect a neural injury, rapid diagnosis and treatment are needed. MRI and CT-scan examination are the best of choice in imaging neural injury. Mild symptoms without objective neural deficit, mostly showed good prognosis and whenever they are deteriorate, a neurologic consultation must be done. Lesion with moderate or severe deficit neulogic is an indication for advanced neurologic consultation, neurophysiologic examination (neural conduction study and electromyography) or MRI/CT Scan examination. A complete or progressive neural deficit needs to be evaluated by a neurologist or neurosurgeon. Neural injury with mild symptoms can be treated with steroid, NSAID, neurotropic vitamins, and physiotherapy. Neural trauma due to compression, needs to be decompressed. Recovery process has a direct relationship with the early decompression treatment.